2012
DOI: 10.1176/appi.ajp.2011.11060886
|View full text |Cite
|
Sign up to set email alerts
|

Attention Bias Modification Treatment for Pediatric Anxiety Disorders: A Randomized Controlled Trial

Abstract: Objective While attention bias modification (ABM) is a promising novel treatment for anxiety disorders, clinical trial data remain restricted to adults. The authors examined whether ABM induces greater reductions in pediatric anxiety symptoms and symptom severity than multiple control training interventions. Method From a target sample of 186 treatment-seeking children at a hospital-based child anxiety clinic, 40 patients with an ongoing anxiety disorder who met all inclusion criteria were enrolled in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
205
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(217 citation statements)
references
References 29 publications
7
205
3
2
Order By: Relevance
“…Future research will need to determine whether effects of attentional re-training to food cues can also be obtained outside the laboratory. For example, home-based delivery of attentional bias modification via the internet has already been trialled in the field of anxiety (Eldar et al, 2012;See, MacLeod & Bridle, 2009). Second, the effects of attentional re-training on biased processing and word stem completions were assessed immediately after training.…”
Section: Discussionmentioning
confidence: 99%
“…Future research will need to determine whether effects of attentional re-training to food cues can also be obtained outside the laboratory. For example, home-based delivery of attentional bias modification via the internet has already been trialled in the field of anxiety (Eldar et al, 2012;See, MacLeod & Bridle, 2009). Second, the effects of attentional re-training on biased processing and word stem completions were assessed immediately after training.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent research has extended ABM training to anxiety reduction in children, as well. In a recent randomized control trial, clinically anxious children who demonstrated attention biases for threat were either assigned to an ABM condition or one of two control conditions [64]. After four training sessions over four weeks, only the children in the ABM condition showed reduced attentional biases and anxiety symptoms as measured in both clinician interviews and on a DSM-IV anxiety severity scale measured in a post-treatment session.…”
Section: Individual Differences In Affect-biased Attentionmentioning
confidence: 99%
“…Some of these interventions have been configured to modify processing biases that favour negative emotional information (cf., MacLeod & Clarke, 2015;Lowther & Newman, 2014), for example by training children and young people to shift attention away from environmental threat (e.g. Bar-Haim, Morag, & Glickman, 2011), or to move attention towards positive stimuli (e.g., Eldar et al, 2012). Other interventions instead have been configured to enhance attentional control (e.g., Roughan & Hadwin, 2011;Hadwin & Richards, 2016; see also Owens, Koster & Derakshan, 2013;Sari, Koster, Pourtois & Derakshan, 2015 for similar work with adult populations).…”
Section: Translational Implicationsmentioning
confidence: 99%